Automatic preparation, calibration, and simulation of deformable objects - Morris, Dan; Salisbury, Kenneth (Computer methods in biomechanics and biomedical engineering, 2008)
Many simulation environments - particularly those intended for medical simulation - require solid objects to deform at interactive rates, with deformation properties that correspond to real materials. Furthermore, new objects may be created frequently (for example, each time a new patient's data is processed), prohibiting manual intervention in the model preparation process. This paper provides a pipeline for rapid preparation of deformable objects with no manual intervention, specifically focusing on mesh generation (preparing solid meshes from surface models), automated calibration of models to finite element reference analyses (including a novel approach to reducing the complexity of calibrating nonhomogeneous objects), and automated skinning of meshes for interactive simulation.